Comedy Ballet as Social Commentary : Till Eulenspiegel (1916) - Järvinen, Hanna (My University, 2014)
In 1916, during the American tours of the Ballets Russes company, Vaslav Nijinsky created a choreography to Richard Strauss's tone poem Till Eulenspiegels lustische Streiche, nach alter Schelmenweise, in Rondo Form (1894-1895). Only performed during the tour, the work was long deemed a failure or an indication of the choreographer's approaching insanity. Tracing the reviews and other contemporary materials, this article asks what can be known of a past performance and rehearsal practice - and what our interpretations of the past reveal of present-day concerns and assumptions about dance as an art form.
Keywords: Dance.; Ballets Russes; Nijinsky, Vaslav; tanssi; tanssiteokset; dans; dansverk